Corrigendum to “How to score sedation and adjust the administration rate of sedatives in horses: a literature review and introduction of the Ghent Sedation Algorithm” [Vet Anaesth Analg 46 (2019) 4–132]’, (S1467298718302174), (10.1016/j.vaa.2018.08.005) - Stijn, Schauvliege; Charlotte, Cuypers; Anneleen, Michielsen; Frank, Gasthuys; Miguel, Gozalo-Marcilla [UNESP] (Elsevier, 2022)
The authors regret that an error was included in their published paper. In the legend of Table 3 on p.10 and in the last paragraph of the results on p. 11, the administration rate for detomidine was wrongly expressed per minute, this should have been per hour. • In the legend of Table 3, it is wrongly stated ‘for detomidine, changes by 2.5 μg kg-1 min-1 are proposed’ and ‘for detomidine, changes by 5 μg kg-1 min-1 are proposed’. These should respectively read ‘for detomidine, changes by 2.5 μg kg-1 hour-1 are proposed’ and ‘for detomidine, changes by 5 μg kg-1 hour-1 are proposed’. • In the last paragraph of the results, it is wrongly stated ‘for detomidine, changes in the rate by 2.5 μg kg-1 minute-1 are proposed, since the initial rate of detomidine infusion for standing surgical procedures of the authors is usually around 10 μg kg-1 minute-1’. This should read: ‘for detomidine, changes in the rate by 2.5 μg kg-1 hour-1 are proposed, since the initial rate of detomidine infusion for standing surgical procedures of the authors is usually around 10 μg kg-1 hour-1’. The authors apologize for any inconvenience caused.